The Link Between the Business Process Management Capabilities and the Benefits Created by Robotic Process Automation in an Organisation - Stravinskienė, Inga (Vilnius University Open Series, 2022)
In the context of the Fourth Industrial Revolution, as organisations are increasingly confronted with unclear and complex business environments, digital technologies are being used to acquire and maintain dynamism, innovation, responsiveness to changing societal needs, and agility, which are essential in this time of changes. In the current competitive environment, organising the performance of an organisation solely on the basis of functions and assignments is no longer appropriate. There is a growing interest in the concept of the process-oriented organisation (Szelagowski, & Berniak-Woźny 2020) and a growing focus on the digitalisation of operations and business processes (Kirchmer 2017; Siderska 2020). This article aims to define the link between the essential aspects of the Business Process Management capabilities and the benefit generated by Robotic Process Automation based on theoretical insights.